Formation of pyramidal etch hillocks in a Kossel crystal - Suárez, M. P. (2005)
Surface roughening due to anisotropic etching was studied experimentally and modeled using the Monte Carlo method for a Kossel crystal.  Simulations were used to explore a possible formation mechanism for the appearance of etch hillocks in two and three dimensions.  Similarities with pyramidal etch hillocks that are regularly observed in anisotropic etching of Si(100) are discussed.